2013
DOI: 10.1186/1743-8977-10-38
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary transport of MWCNT following inhalation exposure

Abstract: BackgroundInhalation exposure studies of mice were conducted to determine if multi-walled carbon nanotubes (MWCNT) distribute to the tracheobronchial lymphatics, parietal pleura, respiratory musculature and/or extrapulmonary organs. Male C57BL/6 J mice were exposed in a whole-body inhalation system to a 5 mg/m3 MWCNT aerosol for 5 hours/day for 12 days (4 times/week for 3 weeks, lung burden 28.1 ug/lung). At 1 day and 336 days after the 12 day exposure period, mice were anesthetized and lungs, lymph nodes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
163
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(171 citation statements)
references
References 43 publications
(72 reference statements)
6
163
0
2
Order By: Relevance
“…Translocation to the blood circulation could provide a mechanism for a direct particle effect on the cardiovascular system as an explanation for epidemiological findings of cardiovascular effects associated with inhaled ambient ultra fine particles [24][25][26]. All these above studies were supported our results for translocation and extrapulmonary toxicity induced by the test CNMs.…”
Section: Discussionsupporting
confidence: 88%
“…Translocation to the blood circulation could provide a mechanism for a direct particle effect on the cardiovascular system as an explanation for epidemiological findings of cardiovascular effects associated with inhaled ambient ultra fine particles [24][25][26]. All these above studies were supported our results for translocation and extrapulmonary toxicity induced by the test CNMs.…”
Section: Discussionsupporting
confidence: 88%
“…Others, such as the semi-metallic oxides investigated in this study and carbon-based nanomaterials 24,27 , may be more challenging due to their elemental composition, shape, and depending on the matrix. In two murine inhalation studies by Mercer et al, a similar system to the one employed in this study was used in order to locate carbon nanotubes in the lung and in secondary organs based on their remarkably high contrast with surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, well‐dispersed MWCNTs might be more toxic and show more widespread organ distribution than aggregated MWCNTs, although published data have not indicated that dispersion affected the toxicity of TiO 2 nanoparticles (Kobayashi et al ., 2009). However, there are a few previous studies that have investigated the biodistribution of well‐dispersed MWCNTs for observation periods of over 6 months (Mercer et al ., 2013; Czarny et al . 2014,).…”
Section: Discussionmentioning
confidence: 99%
“…After inhalation exposure and intratracheal instillation to original and functionalized MWCNTs, no clearance was observed within 21 days (Silva et al ., 2014). After inhalation exposure, 25% and 35% cleared at 168 and 336 days post‐exposure compared with the burden at 1 day post‐exposure in rats (Mercer et al ., 2013). In contrast, spherical C 60 nanoparticles were cleared from the lungs much faster than MWCNTs [half‐life < 1 month (Shinohara et al ., 2010)] although C 60 and CNTs are both carbon allotropes, and both have a graphene structure.…”
Section: Discussionmentioning
confidence: 99%